1965
DOI: 10.1002/asi.5090160405
|View full text |Cite
|
Sign up to set email alerts
|

Comparative indexing: Terms supplied by biomedical authors and by document titles

Abstract: The original aim of this study was to obtain objective data bearing on the much argued question of whether author indexing is “good.” Author indexing of 285 documents reporting biomedical research was scored by comparing the author‐supplied terms (author set) for each paper with a criterion set of terms that was established by asking a group of 12 potential users to describe the same document. Terms in the document title (title set) were scored similarly. The average author set contained almost half of all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A few studies have examined author keywords (Schultz, Schultz and Orr 1965;Kipp 2005;Gil-Leiva and Alonso-Arroyo 2007;Kipp 2007b;Strader 2009;Kipp 2011) while a few additional studies have examined title keywords (Bloomfield 1966;Voorbij 1989;Frost 1989;Ansari 2005, Jeong 2009. Schultz, Schultz and Orr (1965) examined author keywords and title keywords for 285 biomedical articles submitted for publication and found that author terms were more likely than title terms to match the controlled vocabulary terms. Kipp (2005) examined tags, author keywords and descriptors and found that while many tags matched descriptors or author keywords exactly there were also substantial differences.…”
Section: Related Studiesmentioning
confidence: 99%
“…A few studies have examined author keywords (Schultz, Schultz and Orr 1965;Kipp 2005;Gil-Leiva and Alonso-Arroyo 2007;Kipp 2007b;Strader 2009;Kipp 2011) while a few additional studies have examined title keywords (Bloomfield 1966;Voorbij 1989;Frost 1989;Ansari 2005, Jeong 2009. Schultz, Schultz and Orr (1965) examined author keywords and title keywords for 285 biomedical articles submitted for publication and found that author terms were more likely than title terms to match the controlled vocabulary terms. Kipp (2005) examined tags, author keywords and descriptors and found that while many tags matched descriptors or author keywords exactly there were also substantial differences.…”
Section: Related Studiesmentioning
confidence: 99%
“…The data used in this investigation came from two sources. One source of data was a study performed by Schultz, Schultz and Orr (11) in which 285 biomedical documents were indexed by the author, by twelve biomedical scientists who were engaged in research in the area, and by eight professional indexers. For the purposes of this study, data from 29 of these documents was used.…”
Section: Experimental Datamentioning
confidence: 99%
“…Inter-indexer consistency studies all point to high levels of inconsistency. Foundational studies on this topic go back to the 1960s, exemplified by the research undertaken by Zunde and Dexter (1969), whose analysis of earlier data (Schultz, Schultz, & Orr, 1965) pointed toward "power laws" and fuzzy sets as explanatory devices. Cooper's (1969) contemporary study questioned of the importance of consistency.…”
Section: Previous Research 21 Inter-indexer Consistencymentioning
confidence: 99%